The Roman High- and Low-Avoidance Rat Lines Differ in the Acquisition, Maintenance, Extinction, and Reinstatement of Intravenous Cocaine Self-Administration - Fattore, Liana; Piras, Giovanna; Corda, Maria G; Giorgi, Osvaldo (Neuropsychopharmacology (New York, N.Y.), 2009)
The selective breeding of Roman high- (RHA) and low-avoidance (RLA) rats for, respectively, rapid vs extremely poor acquisition of avoidant behavior in a shuttlebox has produced two phenotypes that differ in temperament traits, in mesocortical/mesolimbic dopamine system function, and in the behavioral and neurochemical responses to the acute and repeated administration of psychostimulants and opiates. The phenotypic traits of the RHA line predict higher susceptibility, compared with RLA rats, to the reinforcing properties of addictive substances like cocaine. The present study was designed to compare the acquisition, maintenance, reinstatement of drug-seeking after long-term extinction, and reacquisition of intravenous cocaine self-administration (SA) behavior in the Roman lines. Compared with RLA rats, the rates of responding during cocaine SA acquisition were higher, extinction from cocaine SA was prolonged, and drug-induced reinstatement of cocaine-seeking behavior was more robust in RHA rats. Moreover, only RHA rats reacquired extinguished lever-pressing activity when a low reinforcing dose of cocaine was available. These findings are consistent with the view that subjects with genetically determined high responsiveness to the acute and chronic (ie, sensitizing) effects of psychostimulants, such as RHA rats, also display a higher propensity to self -administer cocaine. Further comparative studies in the Roman lines, using SA paradigms that distinguish mere drug-taking from the compulsive and uncontrolled drug use that characterizes addiction in humans, may eventually help to characterize the relationships among genotype, temperament traits, and neurobiological mechanisms involved in the individual vulnerability to cocaine addiction.